How servant leadership motivates young university teachers’ workplace well-being: The role of occupational commitment and risk perception - Zeng, Jianji; Lai, Jiahui; Liu, Xiaofan (Frontiers in Psychology, 2022)
Drawing on the integration of social exchange theory and situational power theory, this paper collects 215 data points to analyze the effect of servant leadership on young university teachers’ workplace well-being and explores the mediating effect of occupational commitment and the moderating effect of risk perception on the indirect effects of servant leadership on workplace well-being. Results revealed that servant leadership was positively related to young university teachers’ workplace well-being. Occupational commitment plays a partial mediating role linking servant leadership and young university teachers’ workplace well-being. Risk perception plays a moderating role in the indirect relationship between servant leadership, occupational commitment and workplace well-being. When risk perception has a low level, the mediating effect of occupational commitment is stronger.